Teaching English through English : - Willis, Jane (Longman, 1998)
The book covers the use of social, personal and organisational language in typical classroom situations, and shows how these situations can be used for presenting, practising and reinforcing target language. It also deals with the main ares of methodology, and the language and teaching skills needed for each.